Agriculture, Food Security and Poverty Reduction in Nigeria: Cointegration and Granger Causality Approach : Array - Tochukwu, Obiakor Rowland; Damilola Olanipekun, Wahid; Omoyele, Olufemi Samuel; Aderemi, Timothy Ayomitunde (Acta Universitatis Danubius. Œconomica, 2022)
Provision of sufficient food and elimination of abject poverty have usually been the conventional benefits of agriculture to any society. Meanwhile, despite the fact that Nigeria is an agrarian society, food insecurity and poverty have become the issues of concern among both scholars and policymakers in the recent times. Against this backdrop, this study examined the nexus among agriculture, food security and poverty reduction in Nigeria from 1990 to 2019 within the framework of Cointegration and Granger Causality approach. Data was collected from the Central Bank of Nigeria Statistical Bulletin and the World Development Indicators respectively. The following are the major results that emanated from the study. A long run equilibrium relationship exists among agricultural valued added, food production index and GDP per capita in Nigeria. Similarly, there is a unidirectional causality which flows from food production index to poverty reduction in Nigeria. In the same vein, one way causality flows from poverty reduction to agricultural value added in the country. Consequently, this study makes the following recommendation for the policymakers in Nigeria, and other African countries by extension, that agricultural value added and food production are the important variables that cannot be undermined when poverty reduction occupies the central focus of the policymakers. Therefore, any time these policymakers want to reduce poverty, policies that will drive agricultural value added and food production should be embarked upon.